Właściwość sądu w procesie zwykłym w „Mitis Iudex Dominus Iesus” - Bartczak, Adam (Ius Matrimoniale, 2017)
The new canon 1672 simply reiterates the previous norm that tribunals are competent if they are the tribunals of the place where the marriage was celebrated (an adaption of the ancient notion of the forum of the place where the contract was entered) or the tribunals of the place where the respondent has a domicile or quasi-domicile or the tribunals of the place in which the majority of proofs are to be gathered. This article outlines changes in the law. The author points to the advantages and concerns associated with the new law.